Effect of Different Substituted Fish Meal with Maggot Meal for Growth of Jambal Siam (Pangasius hypopthalmus) - James Panjaitan; Indra Suharman; Adelina ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
The research was conducted from March to April 2014 in experimental pond Fishery and Science Faculty of Riau University. The purposed of the research was to knowed the effect of different substituted fish meal with maggot meal that provide the best growth of Jambal siam (Pangasius hypopthalmus). The experiment was designed by Completely Random design with 5 substitution and 3 replication. The result indicated that differnt substitution fish meal with maggot meal doesn’t have significantely effect on growth of Jambal siam (Pangasius hypopthalmus). The best result was achived by treatment E with 100% Maggot meal level. Total absolute body weight, spesific growth rate and feet efficiency was 30,16 grams, 4,76%/ day, and 69,3% respectively, while the best protein retention and survival rate on treatment C ( 50 % of maggot meal) of 44,52 % and 70 % respectively. Water quality during the research are temperature of 29 – 30 0 C, pH of 5 – 6, and disolved oxygen of 4,5 - 5,4 ppm.Key word :Maggot meal, Fish meal,Jambal siam (Pangasius hypopthalmus)